The mediating role of coping styles in the relationship between fear of COVID-19 and mental health problems: a cross-sectional study among nurses - Nurul Huda; Malissa Kay Shaw; Hsiu Ju Chang; Erwin; Suci Tuty Putri; Satriya Pranata (BMC, 2024)
Abstract Fear of being infected by coronavirus disease 2019 (COVID-19) could trigger mental health problems among nurses at the frontline. In such a situation, coping strategies are needed to deal with the imminent threat. The purpose of this study was to test the mediating effects of coping on relationships of fear of COVID-19 with anxiety, depression and post-traumatic syndrome among nurses who were in contact with COVID-19 patients. A cross-sectional and correlational research design was used to recruit a sample of 278 nurses who treated COVID-19 patients in four government referral hospitals in Indonesia. A bootstrap resampling procedure was used to test the significance of the total and specific indirect effects of coping on relationships of Fear of COVID-19 with anxiety, depression and post-traumatic syndrome. The nurses reported moderate levels of fear of COVID-19, considerable anxiety and depression, and a moderate level of coping. We found coping to be significantly negatively correlated with the reported levels of anxiety, depression and post-traumatic syndrome (p < 0.001). Coping mediated relationships of fear of COVID-19 on depression, anxiety and post-traumatic syndrome after controlling for relevant confounders for each dependent variable. This shows that enacting coping mechanisms is important to achieve an adaptive effect on nurses' mental health. Proper assessments and interventions should be tailored and implemented for nurses who have contact with COVID-19 patients to facilitate their use of coping strategies when needed in stressful situations.